Memantine and Its Combination with Acetylcholinesterase Inhibitors in Pharmacological Pretreatment of Soman Poisoning in Mice - Kassa, Jiri; Karasova, Jana Zdarova (Neurotoxicity research, 2021)
Nerve agents pose a real threat to both the military and civil populations, but the current treatment of the poisoning is unsatisfactory. Thus, we studied the efficacy of prophylactic use of memantine alone or in combination with clinically used reversible acetylcholinesterase inhibitors (pyridostigmine, donepezil, rivastigmine) against soman. In addition, we tested their influence on post-exposure therapy consisting of atropine and asoxime. Pyridostigmine alone failed to decrease the acute toxicity of soman. But all clinically used acetylcholinesterase inhibitors administered alone reduced the acute toxicity, with donepezil showing the best efficacy. The combination of memantine with reversible acetylcholinesterase inhibitors attenuated soman acute toxicity significantly. The pretreatment administered alone or in combinations influenced the efficacy of post-exposure treatment in a similar fashion: (i) pyridostigmine or memantine alone did not affect the antidotal treatment, (ii) centrally acting reversible acetylcholinesterase inhibitors alone increased the antidotal treatment slightly, (iii) combination of memantine with reversible acetylcholinesterase inhibitors increased the antidotal treatment more markedly. In conclusion, memantine alone failed to decrease the acute toxicity of soman or increase post-exposure antidotal treatment efficacy. The combination of memantine with donepezil significantly increased post-exposure effectiveness (together 5.12, pretreatment alone 1.72). Both drugs, when applied together, mitigate soman toxicity and boost post-exposure treatment.
Keywords: Donepezil; Memantine; dopaminové látky; Soman; soman; zvířata; myši; Antiparkinson Agents; cholinesterasové inhibitory; Mice; Rivastigmine; donepezil; Dopamine Agents; Male; Acetylcholinesterase; antiparkinsonika; Pre-Exposure Prophylaxis; preexpoziční profylaxe; Animals; mužské pohlaví; kombinovaná farmakoterapie; acetylcholinesterasa; Cholinesterase Inhibitors; Drug Therapy, Combination; Pyridostigmine; memantin